(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Tuberculosis is still endemic in developing countries and over the past decades resurgence of this disease has been a major health threat mainly due to increasing frequencies of immunosuppressive states and drug resistance organism. Though it is a lung disease ,intracranial elements become involved in 5-10% of cases either as meningitis or tumour like masses i.e. tuberculoma. Its occurrence during pregnancy is occasional and its clinical picture mimicking toxemia of pregnancy and brain tumor. In addition, the effects of pregnancy on tuberculosis or vice versa have been controversial. We present here a case of a 25 years old lady who presented with severe frontal headache and neck pain associated with vomiting at her 12 weeks of pregnancy. At 20 weeks of pregnancy MRI was done which revealed an extramedullary placed SOL in right fronto temporal region. Craniotomy and excision done and histopathology report was compatible with tuberculosis. Anti TB drug therapy was started at her 26 weeks of pregnancy. Tuberculoma should be considered in differential diagnosis of eclampsia and brain mass particularly in women coming from endemic areas for this infection even in the absence of pulmonary involvement. JCMCTA 2016 ; 27 (1) : 65 - 67